Delayed Cerebral Ischemia following to Repair of Penetrating Trauma to External Carotid artery - Mahdi Eskandarlou; Amir . Derakhshanfar (پزشکی بالینی ابن سینا, 2016)
Introduction: Penetrating trauma to anterior neck can induce cerebral ischemia due to carotid artery injury. Brain ischemia also can present after surgical carotid repairs. Early diagnosis and suitable treatment modality prevent from permanent neurologic deficit post operatively.